Pengaruh Fasilitas Kerja dan Budaya Organisasi terhadap Kepuasan Kerja Karyawan Bagian Produksi di PT. Bumi Mineral Sulawesi - Muh. Farhan Zaki; Muhammad Kasran; Dirham Latief (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The purpose of this study is to examine how work facilities and corporate culture at PT. Bumi Mineral Sulawesi influence job satisfaction among production employees. This research employs a quantitative method with a population of 110 employees and a sample of 52 respondents who agreed to complete the questionnaire. Primary data were collected through online questionnaire distribution and processed using the SPSS data analysis application. Data analysis was conducted to test the hypotheses between the research variables. The results of the study indicate that work facilities have a positive and significant effect on employee job satisfaction, organizational culture also has a positive and significant effect on job satisfaction, and both variables simultaneously have a positive influence on job satisfaction. Therefore, improving workplace facilities and fostering a positive corporate culture can serve as important strategies to enhance job satisfaction among manufacturing employees at PT. Bumi Mineral Sulawesi.